If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 41 = 3x + 17 Reorder the terms: 41 + -1x = 3x + 17 Reorder the terms: 41 + -1x = 17 + 3x Solving 41 + -1x = 17 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 41 + -1x + -3x = 17 + 3x + -3x Combine like terms: -1x + -3x = -4x 41 + -4x = 17 + 3x + -3x Combine like terms: 3x + -3x = 0 41 + -4x = 17 + 0 41 + -4x = 17 Add '-41' to each side of the equation. 41 + -41 + -4x = 17 + -41 Combine like terms: 41 + -41 = 0 0 + -4x = 17 + -41 -4x = 17 + -41 Combine like terms: 17 + -41 = -24 -4x = -24 Divide each side by '-4'. x = 6 Simplifying x = 6
| -3n^2=-141 | | 5x-1=5+2x | | 10v^2=-9 | | 5x(6y*4x)=65 | | (x)(2x)=28x | | 12+n=-17 | | -8-4(1+6f)=-33 | | 4x+1-(6)=3+2x | | 5(4)-10y=20 | | 2/-7/-4= | | 3x+7-2x-1=x+10 | | X-2+x-2=x+3 | | -2(4s-5)-10=-2(9s+8)-3 | | 5(3)-10y=20 | | 5x(x)+75+5=2x+52 | | (2x+2)(2x+2)=168 | | 17=3(a+3)-a | | 5(1)-10y=20 | | 28x^2-68x=48 | | 19(4c-1)-8=74c+19 | | 127+8d=19+20d | | 5(-1)-10y=20 | | 2b^2-14b=b-7 | | 0=9x^2+3x-2 | | x^3+-3x^2+-22x=-24 | | 2(3x+5)+22=-4(2x-15) | | 5(-2)-10y=20 | | (6y+7)-(6+5y)=9 | | Y=4-5(-1) | | 18(v+4)-2v=4(4v+1)-8 | | 2*20-3x= | | 4(-7k+5)=-2-6k |